2019
DOI: 10.1007/s40265-019-01125-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Clinical Attributes of Auryxia® (Ferric Citrate)

Abstract: Chronic kidney disease (CKD) is a major cause of morbidity and premature mortality and represents a significant global public health issue. Underlying this burden are the many complications of CKD, including mineral and bone disorders, anemia, and accelerated cardiovascular disease. Hyperphosphatemia and elevated levels of fibroblast growth factor 23 (FGF23) have been identified as key independent risk factors for the adverse cardiovascular outcomes that frequently occur in patients with CKD. Auryxia ® (ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 95 publications
1
31
0
Order By: Relevance
“…In addition, ferric citrate treatment did not affect serum iFGF23 or serum phosphorus, suggesting that this iron supplementation with 0.3% ferric citrate treatment may not affect phosphorus metabolism. Ferric citrate is an iron-based compound, and has been approved in the USA as a phosphate binder for the control of serum phosphorus levels in adult patients with CKD on dialysis and also as an iron replacement product indicated for the treatment of iron deficiency anemia in adult patients with CKD not on dialysis [7]. It is approved in Japan for the improvement of hyperphosphatemia in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, ferric citrate treatment did not affect serum iFGF23 or serum phosphorus, suggesting that this iron supplementation with 0.3% ferric citrate treatment may not affect phosphorus metabolism. Ferric citrate is an iron-based compound, and has been approved in the USA as a phosphate binder for the control of serum phosphorus levels in adult patients with CKD on dialysis and also as an iron replacement product indicated for the treatment of iron deficiency anemia in adult patients with CKD not on dialysis [7]. It is approved in Japan for the improvement of hyperphosphatemia in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that ferric citrate hydrate led to few serious adverse events in organ systems usually affected by iron overload, and improved iron parameters in patients with CKD and iron deficiency anemia without negatively perturbing serum phosphate [7]. Ferric citrate could be a safe and efficacious treatment for IDA due to the clinical results in patients with nondialysis-dependent CKD [6,7]. From these clinical results mentioned above, there is a possibility that ferric citrate could exert not only phosphate reducing effect but also hematopoietic effect in advanced CKD patients.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…X-ray crystallography reveals that pathway [54] and the mechanisms involving intestinal microflora [55]. Iron citrate complexes have been shown to capture and reduce phosphate and FGF23 levels in both dialyzed and non-dialyzed CKD patients [53]. As phosphates [56] and FGF23 [57] A significant reduction in the requirement for therapy with erythropoiesis stimulating agents was also reported [60].…”
Section: Sucrosomial Ironmentioning
confidence: 96%